The Use and Technique of Sentinel Node Biopsy for Skin Cancer. Issue 5 (26th April 2022) - Upadhyaya, Siddhi N.; Knackstedt, Rebecca W.; Ko, Jennifer S.; Gastman, Brian R.
Abstract : Learning Objectives: After studying this article, the participant should be able to: 1. Understand the indications for and prognostic value of sentinel lymph node biopsy in skin cancer. 2. Learn the advantages and disadvantages of various modalities used alone or in combination when performing sentinel lymph node biopsy. 3. Understand how to perform sentinel lymph node biopsy in skin cancer patients. Summary: Advances in technique used to perform sentinel lymph node biopsy to assess lymph node status have led to increased accuracy of the procedure and improved patient outcomes.